Innovating Regional Revenue Enhancement through Health Service Levies at the Gorontalo Provincial Health Laboratory - Tahir, Hartati; Rachman, Ellys; Van Gobel, Lisda; Malini Ganapathy (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to analyze the contribution of the Regional Health Laboratory (Labkesda) of Gorontalo Province in increasing Regional Original Revenue (ROR) through service innovation and better management. Theoretical framework: The theoretical framework used includes public service innovation, communication in promotion, and management of resources, facilities, and budgets that affect the performance of Labkesda. Literature review: A literature review examines the role of ROR in regional funding and the challenges faced in increasing its contribution through the health sector. Methods: The method used is qualitative descriptive with data collection through observation, interviews, and documentation. Results: The results of the study show that despite several service innovations such as home care and telephone consultation, Labkesda's contribution to ROR is still limited. Socialization strategies through social media and cooperation between agencies are also not effective because communication tends to be one-way. The main obstacles include limited human resources, infrastructure, budget, and competition with private laboratories. Implications: strengthening service innovation, more creative promotion, and improvements in management to increase Labkesda's contribution to ROR, as well as strengthening its role as a modern and competitive health service provider. Novelty: This research also offers new insights into the gap between the concept of public service innovation and its implementation in the field, as well as provides an overview of the factors that hinder the optimal contribution of Labkesda to ROR.